Creativity, an ideal path from Emilio Garroni to Jean Piaget - Pignataro, Maria (Aesthetica Preprint, 2022)
This paper aims to analyse the concept of creativity as a fundamental trait of human behaviour, showing the problematic and complex nature of the instinct/intelligence dichotomy. Within the framework set out by Emilio Garroni, theorist of creativity, in dialogue with Kant’s transcendental philosophy, this paper attempts to show how Piaget’s theory can help us understand creativity as a peculiarity of the intellectual equipment of humankind. It is the main driver of a subject’s adaptation to the world, aimed at promoting survival. The paper also aims to investigate the interdependence between creativity and legality. Piagetian genetic epistemology sheds light on psychogenesis through close comparison with empiricism on the one hand, and innatism on the other. Within it, intelligence is considered as a constructive-creative activity. Thus, an imaginary path is followed from Garroni to Piaget, through an investigation which focuses primarily on the analysis of functional invariants, the complex assimilation-accommodation mechanism, trying to show the Kantian and “quasi-non-Kantian” of Piagetian functional apriorism and grasping the relationship between organism and environment. This study tries to show the existence of a fil rouge between Garroni, Kant and Piaget, investigating the activity of an epistemic subject. Firstly, it analyses Garroni’s theory and the epistemological reading of Kantian philosophy, with particular reference to Third Critique. Secondly, it introduces Piagetian constructivism, showing the central role of the accommodation-assimilation process and focusing on functional interactivism. Finally, the reflection will focus on the question of “questions and questions”, posed by Garroni, and will analyse the Piagetian decentralization of the child in the dialogical dimension with the adult, throwing further light on creativity understood as an adaptive and constructive procedure.